2015
DOI: 10.1002/term.2061
|View full text |Cite
|
Sign up to set email alerts
|

Development of decellularized scaffolds for stem cell-driven tissue engineering

Abstract: Organ transplantation is an effective treatment for chronic organ dysfunctioning conditions. However, a dearth of available donor organs for transplantation leads to the death of numerous patients waiting for a suitable organ donor. The potential of decellularized scaffolds, derived from native tissues or organs in the form of scaffolds has been evolved as a promising approach in tissue-regenerative medicine for translating functional organ replacements. In recent years, donor organs, such as heart, liver, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(127 citation statements)
references
References 121 publications
0
117
0
4
Order By: Relevance
“…Acellular tissues are mainly generated by using physical, enzymatic, and/or chemical mechanisms [9,37,38,39]. Based on its simplicity, the most commonly used method to obtain acellular tissue is immersion and agitation of the sample, in presence of decellularizing agents.…”
Section: Acellular Tissues and Biomaterials For Vml Treatment: Typmentioning
confidence: 99%
See 1 more Smart Citation
“…Acellular tissues are mainly generated by using physical, enzymatic, and/or chemical mechanisms [9,37,38,39]. Based on its simplicity, the most commonly used method to obtain acellular tissue is immersion and agitation of the sample, in presence of decellularizing agents.…”
Section: Acellular Tissues and Biomaterials For Vml Treatment: Typmentioning
confidence: 99%
“…In the literature such scaffolds are defined as decellularized; however, some of them would be better defined as “anucleated” rather than “acellular” scaffolds. Indeed, together with the elimination of the nuclear content and the maintenance of the ECM, such treatments can partially preserve cytoplasmic components of the original tissue, in particular those belonging to myofibers [24,32,33,39,45,46]. …”
Section: Acellular Tissues and Biomaterials For Vml Treatment: Typmentioning
confidence: 99%
“…Thus stem cells can be considered a potent and encouraging cell source for tissue engineering [124]. Accordingly to this concept, Wan et al has just proposed a study about the possibility to culturing iPSCs derived pancreatic β cells on decellularized ECM [125].…”
Section: Small Animal Modelsmentioning
confidence: 99%
“…In addition to its structural complexity, the lung compartments contain up to 60 different types of cells [10]. Despite these difficulties, it has been shown that by using adequate protocols the lung can be decellularized to obtain an almost intact extracellular scaffold [1120]. …”
Section: Reviewmentioning
confidence: 99%